Prevalence and risk factors of functional gastrointestinal disorders in early period medical students: a pilot study in Tunisia. Issue 1 (31st December 2022) - Gallas, Syrine; Knaz, Hend; Methnani, Jaber; Maatallah Kanzali, Mariem; Koukane, Ahlem; Bedoui, Mohamed Hedi; Latiri, Imed
Abstract: Functional gastrointestinal disorders (FGIDs) are highly prevalent in medical students around the world. However, there is no specific data on FGIDs in Tunisia. The objectives of this study were to evaluate the prevalence of FGIDs in medical students according to the rome III criteria and to identify risk factors associated with these disorders. A self-administered questionnaire survey was carried out among the students from the first and the second year of medical studies. We studied the influence of socio-demographic characteristics, lifestyle, health care seeking, psychosomatic symptoms and hospital anxiety and depression scale on the prevalence of FGIDs among these students. Three hundred and forty-three students (20.3 ± 0.8years) were included in our study. The prevalence of FGIDs was 54.2%. The main FGIDs found were the unspecified functional bowel disorder (46.6%), functional constipation (11.6%), irritable bowel syndrome (7.6%) and functional dyspepsia (6.7%). In logistic regression, abnormal BMI (OR = 2.1, 95% CI= 1–4.3), living in school dormitory (OR = 3.7, 95% CI = 1.7–7.8), low water intake (OR = 2.2, 95% CI = 1.1–4.2), digestive medication use (OR = 3.4, 95% CI= 1.3–8.5), and probable or definite anxiety (OR = 2.5, 95% CI = 1.1–5.8) were the five risk factors associated with FGIDs. We demonstrate a high prevalence of FGIDs (54.2%) among our students. Risk factors for FGIDs were abnormal BMI, living in school dormitory, low water intake, digestive medication use and anxiety.